Effort-Based Career Opportunities and Working Time - Massimiliano Bratti; Stefano Staffolani (Institute for the Study of Labor (IZA), 2005)
In this paper we describe the hypothesis of effort-based career opportunities as a situation in which profit maximizing firms create incentives for employees to work longer hours than the bargained ones, by making career prospects dependent on working hours. When effortbased career opportunities are effective, they raise working time and output per worker reducing workers? utility. A first attempt is made to empirically estimate the relationship between hours worked and the expected opportunities of promotion using the British Household Panel Survey data set. Our analysis shows that the perceived probability of promotion increases with working time and that this result is robust to various econometric specifications.
Keywords: J23; M12; J22; J50; 330; bargaining; career; personnel management; promotion; welfare; working time; Erwerbsverlauf; Arbeitszeit; Leistungsanreiz; Verhandlungstheorie; Grossbritannien; Deutschland; Vereinigte Staaten